THE EFFECT OF TAX EXAMINATION, TAX ADMINISTRATION SANCTIONS, UNDERSTANDING TAXATION, AND TAX EMPLOYMENT (TAX AMNESTY) ON COMPULSORY TAX COMPLIANCE PERSONAL AT KPP PRATAMA MEDAN POLONIA - Situmorang, Sakti Fransisco (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to determine the effect of Tax Examination, Tax Administration Sanctions, Understanding of Taxation, and Tax Amnesty on Individual taxpayer compliance in Medan Polonia KPP. This type of research uses associative research that is clausable, namely research that identifies causal relationships between various variables. The data used in this study are primary data in the form of closed questionnaire data. In a closed questionnaire the respondent must choose the answer provided from the questions asked. The sampling used in this study is by nonproability sampling, namely incendental sampling, obtained 100 samples from 165,852 populations. The method of data analysis in this study is Multiple Regression Analysis, then processed using the Statistical Package For Social Science (SPSS) program. The variables used are the dependent variable and the independent variable. The dependent variable in this study is